Mohammad A. Quayum and Grace V. S. Chin (eds.). the postcolonial millennium: new directions in Malaysian Literature in English. Oxfordshire, UK: Routledge, 2024. - Kavitha Ganesan (USM Press, 2025)
The current collection, comprising of nine essays, that was first published as a special issue in the Journal of Postcolonial Writing (Chin and Quayum 2021) departs from Quayum and Wicks’ earlier work, Malaysian Literature in English: A Critical Reader (2001), hence, it is a stock taking effort 20 years after the Malaysian Anglophone tradition was first categorised as a corpus requiring serious literary attention. Unsurprisingly then, in its introduction, like its predecessor, the collection charts the history and unease that the local English-medium literary works have experienced with the state, its policies and the spill-over effects on the Anglophone writing tradition of the country.